Pengaruh Penerapam Relationship Marketing terhadap Kepuasan Nasabah: Studi pada PT. Bank BNI Syariah Kantor Cabang Bekasi - Rafika Rahmawati (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
The success of the banking world will be fulfilled if it can create customersatisfaction to achieve the goal then the banking company apply RelationshipMarketing. But creating customer satisfaction is not easy then this study aims toanalyze the influence of the implementation of Relationship Marketing to customersatisfaction consisting of three dimensions of the Financial Benefits, Social Benefitsand Confidence Benefits. The method used in this research is quantitativecorrelational. Methods of data analysis of this study using multiple linear regression.The results showed that simultaneously the variables Financial Benefits, ConfidenceBenefits and Social Benefits significantly influence customer satisfaction. PartiallyFinancial Benefits and Confidence Benefits have no significant effect on customersatisfaction, BNI Syariah should pay more attention and improve Financial Benefitsand Confidence Benefits to create optimal customer satisfaction while SocialBenefits partially significantly influence customer satisfaction BNI Sharia Bank canimprove customer satisfaction with more emphasis on Social Benefits variable.